Comparison Of Design And Costs Between Bridge Construction Using WF And Precast Concrete Profile - Elisa Sarmento Soares; Julistyana Tistogondo (Journal of World Conference (JWC), 2020)
The bridge that will be planned is resettled in Manatuto, with a span of 100 m and a width of 9.74 m. In this Final Project Preparation, the Sahen Soibada Bridge was redesigned using Girder I beams with a cross section height of 2300 mm, prestressive concrete quality K 300 and Fc ’41.5 Mpa Calculation of loading on the bridge using SNI 1725: 2015, Analysis of the load that occurs is analysis of dead load, additional dead load, live load, wind load and analysis of the influence of time such as crawling and shrinkage and loss of prestressing. Then the results of the analysis carried out stress control that occurred in the structure. As well as for the structure of the budget for the 100 m WF Baja bridge that is equal to US $ 3,384 214.13 while for Concrete that is equal to 3,070,804.08.